Charles Withers papers - Withers, Charles, 1889?-1947.
Scripts, theatrical programs, scrapbooks, clippings, handbills, broadsides, and other papers relating to Withers's career in vaudeville and the theater and various revues in which he appeared.
Library of Congress Prints and Photographs Division of the Library.
Vaudevillian and humorist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Revues -- United States; Theater -- United States; Vaudeville -- United States; Actors; Humorists